2007
DOI: 10.3144/expresspolymlett.2007.28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal and hygrothermal aging on the plane stress fracture toughness of poly(ethylene terephthalate) sheets

Abstract: Abstract. The in-plane (plane stress) fracture toughness of two polyester (PET, PETG) sheets were assessed using the essential work of fracture (EWF) method after thermal and hygrothermal aging performed just below glass temperature. This ensured that physical aging takes place. On the aged sheets the yield stress (σy), enthalpy relaxation (ΔH) and EWF parameters were determined. It was observed that the essential work of fracture component related to the specific yielding (we,y) is suitable for assessing phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 16 publications
(25 reference statements)
0
13
1
Order By: Relevance
“…Nevertheless, there are few works describing the effect of physical aging on the fracture behaviour of PLA using Fracture Mechanics approaches. It has been shown that the EWF methodology is a useful tool to investigate the effect of physical aging on PET and Glycol-modified Poly (ethylene terephthalate) (PETG) films [14][15][16]. In the case of PLA, which has faster physical aging than PET and PETG, the EWF analysis can only be successfully applied in the non-aged material.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are few works describing the effect of physical aging on the fracture behaviour of PLA using Fracture Mechanics approaches. It has been shown that the EWF methodology is a useful tool to investigate the effect of physical aging on PET and Glycol-modified Poly (ethylene terephthalate) (PETG) films [14][15][16]. In the case of PLA, which has faster physical aging than PET and PETG, the EWF analysis can only be successfully applied in the non-aged material.…”
Section: Introductionmentioning
confidence: 99%
“…The sudden cooling freezes this less ordered structural state and hampers a chain reorganization such as the one caused by aging during slow cooling. Even though physical aging on toughness behaviour of polymers has been little investigated using fracture mechanics approaches, the essential work of fracture method (EWF) has been reported as a successful technique to follow the effect of physical aging on polymer films [12][13][14][15][16]. The aim of this work consists in the application of a de-aging thermal treatment to two commercial grades of PLA with different D-lactic monomer fractions and studying their fracture behavior applying the EWF method.…”
mentioning
confidence: 99%
“…Except for a ligament length equal to 8 mm, all the sample dimensions are in the validity domain of the EWF method, as analyzed in the literature [11,14,16,32]. The specimens were drawn using a Zwick machine at 2 mm min −1 , a crosshead speed currently used in recent work (e.g., [27,29]). They were tested in the controlled laboratory conditions: temperature 23°C, relative humidity 50%.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Many polymers have been characterized by this technique: polyethylene [14][15][16], polypropylene [17,18], polyamide 6 [19] and 6-6 [14,16], poly(ethylene terephthalate) and copolymers [16,[20][21][22][23][24][25][26][27][28][29], poly(ethylene naphthalate) [30,31], polycarbonate [32], etc. The EWF method is able to detect environment effects, such as hygrothermal aging in hygroscopic polymers like poly (ethylene terephthalate) [27,29]. The essential work of fracture is also sensitive to morphological parameters, such as cristallinity [16,21] or molecular orientation [25,32].…”
Section: Introductionmentioning
confidence: 99%